Pneumocystis jirovecii Colonization in Non-HIV-Infected Patients Based on Nested-PCR Detection in Bronchoalveolar Lavage Samples. - Hossein Khodadadi; Hossein Mirhendi; Mehdi Mohebali; Parivash Kordbacheh; Hossein Zarrinfar; Koichi Makimura (Tehran University of Medical Sciences, 2013)
Pneumocystis jirovecii causes Pneumocystis pneumonia (PCP) in immunocompromised patients with a high rate of morbidity and mortality. Colonization with this fungus may stimulate pulmonary inflammation or lead to PCP in susceptible patients. The epidemiology of this infection and routs of its transmission has poorly studied in Iran. We examined Pneumosystis colonization in patients with various lung underlying diseases.Bronchoalveolar lavage (BAL) fluids of 458 patients with different underlying diseases or pulmonary signs were collected between August 2010 and January 2012. Patients were divided into four groups: transplant recipients, malignant patients, immunosuppressive drug recipients and patients with other different lung diseases. A sensitive nested-PCR method targeted 18S ribosomal RNA gene was used for investigating P. jirovecii in the specimens.P. jirovecii DNA was detected in 57 out of 458 (12.5%) BAL samples by nested-PCR. Colonization rate in malignant patients, transplant recipients, immunosuppressive therapy recipients and patients with other various lung diseases was 21.7%, 20.3%, 12.7% and 7.3%, respectively. The enzyme BanI cuts all PCR products producing fragments with the size of 228 and 104 base pair. This finding as well as sequencing of four random positive samples validated and reconfirmed the PCR results. P. jirovecii cysts were found in 5 out of 57 PCR positive samples.A significant number of patients with pulmonary diseases were colonized by P. jirovecii that can develop to PCP in these patients or they may transmit the fungus to other susceptible patients.